Terrorism and Human Rights: The Nigerian Experience - Agbonika, Josephine Aladi Achor (NIU Journal of Humanities, 2017)
Terrorism is a trend that violators worldwide have used to settle scores with nations over supposed grievances. Each act of terrorism comes with attendant human and property losses, intimidations, threats and crimes of all sorts which may sometimes be regretted after so many terrorist attacks and losses. Terrorism clearly has a very real and direct impact on human rights, with devastating consequences for the enjoyment of the very rights which the government seeks to protect, such as, the right to life, liberty and physical integrity of victims. In addition to these individual costs, terrorism can destabilize Governments, undermine civil society, jeopardize peace and security, and threaten social and economic development. All of these also have serious impacts on the enjoyment of human rights. Terrorism is therefore a global threat to democracy, rule of law, human rights and stability, and since these stand against everything the United Nations stand for, they have since the 11 September, 2001 terrorist attacks in New York and Washington made counter terrorism a way forward in fighting against unnecessary display of anger or grievances. In a bid to fight terrorist attacks by individuals, the State could also indulge in human right breaches which can amount to terrorism. The need for a proactive approach by the state in the protection of human rights against terrorist acts as well as state counter-insurgency expedition is what this work seeks to pinpoint as human right breaches. Keywords: Human Rights, Boko Haram, Terrorism, Terrorist Act